Improving organizational performance through strategic fit of it-business strategic alignment - Anuar, Herman Shah (United Kingdom, 2017)
Understanding different organizational elements (such as strategy, structure, processes, function and environment), their mutual encouragement and creating resemblance among them is an important determinant of organizational performance. The necessity of creating a fit among these elements and creating such complex relationship, raises the question of how to enhance overall organizational performance by aligning different organizational elements. This study will analyze the issue and influence of strategic fit on organizational performance. The strategic fit among elements of an organization can be evidenced by the degree to which strategy, structure, processes, function and environment complement one another.The elements reinforce each other and this can result in a cycle of mutual cause and effect that tightens the relationship among them and produce organizational performance. This paper aimed to give some additional insights into creating strategy-structure fit and to prove once more itscontribution and importance for organizational performance. This paper investigated fit through strategy, structure and strategy implementation process fit, as well as performance and offers an in-depth theoretical and empirical view of strategic fit and raises some additional questions which could be further analyzed in future research on this subject.